Impact of Green Manuring on Health of Low Fertility Calcareous Soils - Asifa Naz; Ansa Rebi; Raheela Naz; Muhammad Usman Akbar; Ana Aslam; Amina Kalsom; Abid Niaz; Muhammad Ibrar Ahmad; Shahrish Nawaz; Rizwana Kausar; Baber Ali; Muhammad Hamzah Saleem; et al. (Land, 2023)
This study was conducted in a rice-based cropping scheme to investigate the impact of green manuring on soil health, considering soil physicochemical properties and sustainable crop production. A field experiment was started on 2 November 2015 and completed on 15 April 2018 under a rice–berseem (Trifolium alexandrinum) cropping system in calcareous soil. Two green manuring patterns, rice–berseem and rice–wheat–sesbania (rostrata), were compared with a commonly practiced rice–wheat (Oryza sativa-Triticumaestivum) cropping pattern. Green manuring of the berseem crop (last cutting) along with 50, 75, and 100% of the recommended fertilizer doses of nitrogen, phosphorus, and potassium (NPK) were compared with recommended NPK fertilization along with control (no fertilizer). The plant growth parameters of rice, including plant height, tillers per plant at maturity, and yield data, were recorded at harvest. The pre-sowing soil analysis revealed that the experimental soil was low in salts, and the nutrient (NPK) status was very low. The results indicated that green manuring substantially enhanced the grain and straw yield of rice crops. Green manuring combined with 75% of recommended NPK produced the highest grain yield (5.83 t ha−1 in year III) compared to the other treatments. The soil analysis showed that the bulk density was reduced while soil porosity, organic carbon, and N, K, and P contents were significantly improved. From the results of this study, it is recommended that under calcareous soil conditions, the regular use of green manuring can significantly improve crop growth, yield, and physicochemical properties of soil and, therefore, should be adopted by farmers.